Calpain Inhibitor SNJ-1945 Attenuates Events Prior to Angiogenesis in Cultured Human Retinal Endothelial Cells - Ma, Hong (Mary Ann Liebert, Inc., 2009)
PURPOSE: Vascular endothelial growth factor (VEGF) is an important regulator of angiogenesis and microvascular permeability. VEGF-induced cytoskeletal reorganization plays a crucial role in angiogenesis. Cytoskeletal organization in endothelial cells is regulated by calpain proteases (EC 3.4.22.17). Calpains are a family of 14 calcium-regulated, intracellular cysteine proteases, which modulate cellular functions by limited, specific proteolysis. Calpain 1 (μ-calpain) and calpain 2 (m-calpain) are the 2 major typical calpain isoforms and are responsible for most calpain activity in endothelial cells. The purpose of the present study was to determine if an orally available form of calpain inhibitor, SNJ-1945, prevented angiogenesis induced by VEGF in cultured retinal endothelial cells. METHODS: Human retinal microvascular endothelial cells (HRMEC) were incubated with VEGF (60–100 ng/mL) for 24 h. Calcium uptake was measured with Fluo8. Total calpain activity was measured using fluorescent-labeled casein substrate, and separate activities for calpains 1 and 2 were assessed by casein zymography. Proteolysis of endogenous calpain substrate α-spectrin in situ was analyzed by immunoblotting. Angiogenesis in vitro was evaluated by measuring cell migration and tube formation into Matrigel. RESULTS: Incubation of HRMEC with VEGF resulted in calcium uptake, increased activity of mainly calpain 2, and increased calpain proteolysis of α-spectrin. Treatment of endothelial cells with calpain inhibitor SNJ-1945 reversed VEGF-mediated tube formation and cell motility. CONCLUSIONS: Inhibition of angiogenesis by specific calpain inhibitor in the presence of VEGF supported our hypothesis that calpains may be involved in VEGF-mediated angiogenesis in retinal endothelial cells. Therefore, manipulating calpain activity by calpain inhibitor SNJ-1945 might provide a promising therapy for management of pathological angiogenesis, such as that occurring in proliferative retinopathy and age-related macular degeneration with neovascularization.